(untitled) (Global Journal of Management and Business Research, 2021)
This research studies the factors that impact the behavior of the consumers of social media buyers. The retail business has changed radically over the most recent two decades, at first with the landing of computer-interface shopping and, more recently, with the emerging of mobile channels and social media stages. It is hard for e-commerce or e-retail companies to identify and influence the variables that drive consumers’ attitudes and behavior. Different types of media affect people’s conclusions, significantly depending on how much time they spend on such media. Facebook and Twitter are two examples of relatively older types of social media in correlation with newer social media networks, for example, Instagram. Furthermore, people use each type of social media for different purposes and based on their individual preferences.